Boardroom governing dynamics: A case study of state-owned oil and gas joint ventures in Egypt - Gharib, Aliaa Ali (AUC Knowledge Fountain, 2015)
The aim of the thesis is to investigate the differences in perceptions towards corporate governance practices on the boards of joint ventures between international or domestic private firms and Egyptian state-owned companies using the oil and gas industry as a case study. A questionnaire was distributed to 13 oil and gas joint venture companies where 100 board members completed the survey. The study reveals the barriers hindering board effectiveness between the domestic and international board members. The differences towards governance practices do exist between local- Egyptian board members who represent the state as an owner, Egyptians representing the private partner, and foreign board members or joint venture boards. The results of the questionnaire shows that nearly half of foreign board members are not satisfied with the board composition and the capabilities of the directors which are considered an important factor in achieving board effectiveness. Nearly half of the Egyptian board members representing the private partner support the view that that the board is not allowed having an access to information in the right time, in contrast to the views of their foreign counterpart. In addition, there is a need for board members to dedicate more time to strategy, performance, talent, and risk management. Nearly half of the foreign board members support the bringing of independent directors into their boards. As for the agenda and materials preparation given to board, almost half of the foreign board members see the need for improving the preparation of board meeting materials and for actively engaging in discussions during the meetings to achieve board efficiency.